Conformal microstrip slot antenna with an AMC reflector for hyperthermia - Singh S.; Sahu B.; Singh S.P. (My University, 2025)
This paper presents the simulation and experimental studies of a conformal microstrip slot antenna integrated with artificial magnetic conductor (AMC) for hyperthermia application. In the proposed applicator, an AMC consisting of an array of modified ring patches on a grounded dielectric substrate is located at optimized distance (=4 mm) from the microstrip slot antenna for improved performance of the applicator. The feed configuration of the proposed slot antenna consists of tapered microstrip line with curved tuning stub. The slot and feed configurations of the antenna are modified to widen its bandwidth so that changes in dielectric property of biological phantom medium can have minimal effect on its operating frequency and impedance bandwidth. In addition, the applicator with modified slot and feed arrangement provides enhanced heating depth in the phantom muscle medium. Provision for cooling of tissue surface is made by providing air gap between the slot antenna and phantom muscle medium. Moreover, the presence of AMC not only reduces the backfield but also enhances the penetration depth in the medium. Additionally, performance comparison of the proposed antenna–AMC and the antenna–perfect electric conductor(PEC) combinations in terms of input characteristics and specific absorption rate (SAR) parameters is also made. Finally, the effects of change in the radius of curvature of the substrate and bio-model on effective field size (EFS) for both homogeneous and tri-layered bio-models are also investigated. It is demonstrated through thermal simulation that temperature above 41 °C exists in the irregular-shaped tumor, which is embedded in the muscle region of the curved/planar tri-layered bio-model near its surface. © 2016 Informa UK Limited, trading as Taylor & Francis Group.